THE EFFECT OF PRODUCTION COSTS AND SELLING PRICES ON NET PROFIT (CASE STUDY ON HARUM MANIS DIO HOUSEHOLD INDUSTRY, CIGADUNG VILLAGE, BREBES REGENCY) - Roni Roni; Hidayati Cahyani Eka Putri (Jurnal Ekonomi, 2022)
The purpose of this study is to analyze the effect of production costs and selling prices on increasing sales profits in the Harum Manis Dio business. The population in this study is the bookkeeping per month of Harum Manis Dio business including production costs, selling prices and net profit. The object of this study is the financial statements of the Harum Manis Dio business in 2020-2021. The method of research approach is used quantitatively, which is based on the philosophy of positivism. This study used purposive sampling technique. The hypothesis testing used is multiple linear regression analysis. The results of this study show that production costs do not have a significant effect on net profit, selling prices have a significant effect on net profit, production costs and selling prices simultaneously have a significant effect on net profit